Morphological characterization of the local goat population “Beni Arrous” - Hilal B.; El Otmani S.; Chentouf M.; Boujenane I. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
A total of 106 goats (10 bucks and 96 does) in 21 farms chosen at random in two districts of Beni Arrous and Rommani were used for description and measurements. Goats studied had stains on their coat, red for two thirds and black for one third of them. The adult goat weighed in average 37.5 kg, the size (height at withers) averaged 63.6 cm and the total body length 64.4 cm. The buck weight averaged 41.8 kg, the height at withers 65.2 cm, and its total body length 60.8 cm. A proportion of 51.4% of goats had a dressed ears form, 76% had no tassels and 57.3% did not have a beard. The presence of horns is dominant in males and females. The chest is prominent; the heart girth is of 79.5 cm.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)